Application of primary sutureless repair for obstructed total anomalous of pulmonary venous connection at the Vietnam National Children’s Hospital - Nguyen, Ly Thinh Truong; Hoang, Thanh Son (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2022)
Objectives: This study evaluates the results of applying primary sutureless technique in surgical repair of total anomalous pulmonary venous connection at Children Heart Center, Vietnam National Children’s Hospital. Methods: A retrospective study was conducted to evaluate the short-term outcomes of primary sutureless repair for all patients diagnosed with obstructed total anomalous venous connection (TAPVC) from July 2015 to December 2016. Results: There were 25 patients undergoing primary sutureless repair during the study period. The mean age and the mean weight are 77.00 ± 23.26 days and 3.93 ± 1.16 kg, respectively. There were 19/25 (76%) cases with preoperative respiratory failure with 14 cases (56%) requiring mechanical ventilation before surgery, of which 9 patients (36%) had life-threatening acute pulmonary edema from before emergency surgical repair. There were 17 cases admitted to the hospital with cardiogenic shock. Evaluation of transthoracic echocardiography showed 15 cases of supracardiac TAPVC, 5 cases of infracardiac TAPVC, 2 cases of intracardiac, 2 cases of mixed, and 1 case of partial TAPVC. The mean aortic cross-clamp time was 65.40 ± 23.34 minutes, the average cardiopulmonary bypass time was 119.72 ± 34.85 minutes, the mean surgery time was 200.04 ± 39.42 minutes. 9 cases underwent circulatory arrest and 7 cases underwent low-flow bypass during surgery. 3 patients died in the postoperative period, of which 2 from septic shock and multi-organ failure, 1 patient from respiratory failure after extubation due to laryngomalacia. The reoperation rate was 2/25 as a consequence of recurrent pulmonary vein stenosis. Conclusions: The primary sutureless repair for obstructed anomalous pulmonary venous connection is safe and favorable. Long-term outcomes follow-up are essentially required.